2012
DOI: 10.1089/jpm.2012.0038
|View full text |Cite
|
Sign up to set email alerts
|

Using Online Learning and Interactive Simulation To Teach Spiritual and Cultural Aspects of Palliative Care to Interprofessional Students

Abstract: This innovative interprofessional educational program combines online learning with live interactive simulation to teach professionally diverse students spiritual, cultural, and interprofessional aspects of palliative care. Despite the challenge of balanced professional representation, this innovative interprofessional educational program met its learning objectives, and may be transferable for use in other educational settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 22 publications
0
68
0
3
Order By: Relevance
“…Educational programs on spiritual and cultural aspects of palliative care and spiritual assessment demonstrated that concepts of spirituality and basics of spiritual assessment may be taught and learned while students were found to develop an understanding and respect for the role of chaplains, social workers and physicians. Evaluation of these programs suggests that this innovative, inter-professional educational course may be transferable for use in other educational settings [50]. In addition to the physical presence of students together in class, online forums enable learners to discuss and outline the contribution of each discipline to spiritual care and holistic care of a patient case study.…”
Section: Intra-professional And/or Inter-professional Education On Spmentioning
confidence: 99%
“…Educational programs on spiritual and cultural aspects of palliative care and spiritual assessment demonstrated that concepts of spirituality and basics of spiritual assessment may be taught and learned while students were found to develop an understanding and respect for the role of chaplains, social workers and physicians. Evaluation of these programs suggests that this innovative, inter-professional educational course may be transferable for use in other educational settings [50]. In addition to the physical presence of students together in class, online forums enable learners to discuss and outline the contribution of each discipline to spiritual care and holistic care of a patient case study.…”
Section: Intra-professional And/or Inter-professional Education On Spmentioning
confidence: 99%
“…4 The acute care setting offers many opportunities for education in palliative care, 28 and online and video education programs have proved effective in developing palliative care knowledge and skills. [29][30][31] To encourage greater uptake of palliative care education opportunities, state licensing boards could encourage or even require palliative care education as part of continuing education requirements.…”
Section: Discussionmentioning
confidence: 99%
“…More studies addressed whether students had learnt about nursing practices through their participation in the simulation (Ellman et al, 2012;Gillan, Parmenter, van der Riet, & Jeong, 2013;Leavy, Vanderhoffy, & Ravert, 2011;Smith, Witt, Klaassen, Zimmerman, & Cheng, 2012). However, studies that included other professions did not report participants recognizing the role of nurses (Ellman et al, 2012).…”
Section: Technical Skillsmentioning
confidence: 99%
“…However, studies that included other professions did not report participants recognizing the role of nurses (Ellman et al, 2012). Again these studies used a variety of simulation scenarios both low and high fidelity.…”
Section: Technical Skillsmentioning
confidence: 99%